Karl Polanyi : The Hungarian writings - Polanyi, Karl, 1886-1964 (Book collections on Project MUSE., 2016)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology and social policy. Newly available in paperback, this volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. Several of the contributions develop Pol.